Nucleation of Organic Molecules via a Hot Precursor State: Pentacene on Amorphous Mica - Winkler, Adolf (American Chemical Society, 2013)
[Image: see text] Organic thin films have attracted considerable interest due to their applicability in organic electronics. The classical scenario for thin film nucleation is the diffusion-limited aggregation (DLA). Recently, it has been shown that organic thin film growth is better described by attachment-limited aggregation (ALA). However, in both cases, an unusual relationship between the island density and the substrate temperature was observed. Here, we present an aggregation model that goes beyond the classical DLA or ALA models to explain this behavior. We propose that the (hot) molecules impinging on the surface cannot immediately equilibrate to the substrate temperature but remain in a hot precursor state. In this state, the molecules can migrate considerable distances before attaching to a stable or unstable island. This results in a significantly smaller island density than expected by assuming fast equilibration and random diffusion. We have applied our model to pentacene film growth on amorphous Muscovite mica.